SOME DATA OF SECOND SEQUENCE NON STANDARD AUSTENITIC INGOT, A2 - Nurdin Effendi; Aziz K. Jahja; . Bandriana (Urania : Jurnal Ilmiah Daur Bahan Bakar Nuklir, 2012)
SOME DATA OF SECOND SEQUENCE NON STANDARD AUSTENITIC INGOT, A2. Synthesis of second sequence austenite stainless steel named A2 using extracted minerals from Indonesian mines has been carried out. The starting materials for austenite alloy consist of granular ferro-scrap, nickel, ferro-chrome, ferro-manganese, and ferro-silicon. The second sequence composition differs from the former first sequence. This A2 sequence contained more nickel, meanwhile titanium element had not been added explicitly to it, and just been found from raw materials contents or impurities, as well as carbon content in the alloy. However before the actual alloying work started, the first important step was to carry out the determination of the fractional amount of each starting material necessary to form an austenite stainless steel alloy as specified. Once the componential fraction of each base alloy-element was determined, the raw materials are weighed on the mini-balance. After the fractional quantities of each constituent have been computed, an appropriate amount of these base materials are weighed separately on the micro scale. The raw materials were then placed in the induction foundry furnace, which was operated by an electromagnetic inductive-thermal system. The foundry furnace system performs the stirring of the molten materials automatically. The homogenized molten metals were poured down into sand casting prepared in advance. Some of the austenite stainless steel were normalized at 600 oC for 6 hours. The average density is 7.8 g cm-1 and the average hardness value of ¢normalized¢ austenite stainless-steels is in the range of 460 on the Vickers scale. The microstructure observation concludes that an extensive portion of the sample’s structure is dendritic and the surface turns out to be homogenous. X-ray diffraction analysis shows that the material belongs to the fcc crystallographic system, which fits in with the austenite class of the alloy. The experimental fractional elemental composition data acquired by OES method turn out to differ slightly from the theoretical assumption. Keywords: data, second sequence, non standard, austenite. BEBERAPA DATA INGOT AUSTENIT NON STANDAR SERI-2, A2. Telah dibuat baja austenitik tahan karat seri-2, yang diberi nama A2, dari bahan-bahan tambang yang digali di Indonesia. Bahan-bahan tambang tersebut berupa ferro scrap, ferro chrome, ferro mangan, ferro silicon dan nikel yang semuanya dalam bentuk granular. Komposisi seri-2 (A2) ini berbeda dari komposisi A1 yang dibuat sebelumnya. Austenitik ini mengandung lebih banyak nikel sedangkan unsur titan tidak lagi ditambahkan secara explisit, melainkan diperoleh dari kandungan atau impuritas-impuritas bahan mentahnya, sebagaimana kandungan karbon. Pembuatan dimulai dengan menghitung porsi bahan-bahan tersebut dari data-data spesifikasi yang diberikan, agar spesifikasi komposisi ingot yang dibuat sesuai dengan yang dikehendaki. Setelah kuantitas dari setiap bahan mentahnya dihitung, maka dilakukan penimbangan. Pekerjaan dilanjutkan dengan memasukkan bahan-bahan tersebut kedalam dapur induksi pengecoran yang memiliki sistem pemanasan induksi elektromagnet. Pengadukan bahan dilakukan secara otomatis dari sistem dapur induksi. Cairan baja yang telah homogen dituang kedalam cetakan pasir. Pada sebagian besar sampel austenitik ini dinormalisir pada 600 oC selama sekitar 6 jam untuk menurunkan kekerasannya. Nilai rapat massa rata-ratanya sekitar 7,8 g cm-1 sedangkan kekerasan rata-rata yang diukur dengan metoda Vickers adalah sekitar 460 VHN. Pengamatan struktur mikro menunjukkan bahwa struktur berupa dendritik dan permukaan bahan relatif homogen secara luas. Pola difraksinya menunjukkan bahwa bahan memiliki struktur kristal fcc yang sesuai dengan baja jenis austenitik. Pengamatan distribusi unsur dilakukan dengan alat optical emision spectrometry (OES) dan hasilnya sedikit berbeda dengan perhitungan teori yang dikehendaki. Kata kunci: data, seri kedua, non standar, austenit.